Politics of reparations: unravelling the power relations in the Herero/Nama genocide reparations claims - Brock, Penohole (Department of Political Studies, 2020)
The Herero/Nama Genocide (1904-1908) under German colonialism in Namibia is the first genocide of the twentieth century and has stirred debates around reparations for historical injustices. Reparative Justice has evolved into a victim-centric pillar of justice, in which perpetrators are legally and morally obligated to pay reparations in its several forms to its victims, including material and symbolic reparations. This thesis is a case study of reparations claims for historical injustices, specifically colonial genocide and explores such claims as a political process. Firstly, defining victims of genocide is a political process in which colonial atrocities have been blanketed by a lawless cover, previously ignoring the rights of the former colonised. The acknowledgement of genocide victims is a not only a necessary step to claiming reparations, but is part of Reparative Justice in which the perpetrator recognises its victims, offers a formal apology and make amends to the victims’ satisfaction. The acknowledgement of the Herero and Nama as victims of genocide has taken over a century for the German government to admit. Secondly, reparations claims is a political process in which requests are demanded and/or negotiated between perpetrator and victim. Germany’s previous foreign policy avoided terms such as 'genocide’ and 'reparations’, which has been a form of colonial amnesia. Namibian actors cannot easily forget the weight of the genocide and have had to negotiate and demand overdue justice in the face of colonial amnesia. Victim groups often do not speak with one voice, as noted in the Herero group, which is divided into general two camps: the Riruako group and the Maherero group. Under Paramount Chief Riruako, and his successor Rukoro, the Ovaherero Traditional Authority (OTA) have made several reparations claims to Germany over the last three decades. The Namibian government has previously played an unsupportive role, due to Germany’s annual development aid, which has undermined the position of the Riruako group. However, Riruako’s Motion on the Ovaherero Genocide in 2006, was unanimously passed and requested that the Namibian government facilitates negotiations between Germany and representatives of the affected communities. The two governments have since entered formal negotiations on how to address the past, however this has been resented by the OTA and some reparations organisations, who argue that the Namibian government have taken the lead on negotiations, rather than facilitate them. Those participating in government negotiations are the Maherero group, and those who have refused to join is the Riruako group, who have lodged a lawsuit in 2017 against the German government for reparations. In 2015, the German government admitted that its shared history with Namibia involved genocide. However, this acknowledgement has transferred limited power to the Namibian actors who continue to be undermined as 'equal’ counterparts to the German government. The German government continue to negotiate on their terms of redress, and have claimed state immunity towards the lawsuit. Therefore, there are small traces of colonial amnesia in Germany’s conduct despite its recent change in foreign policy.